TIPE NARATOR DALAM NOVEL TELEGRAM KARYA PUTU WIJAYA: KAJIAN NARATOLOGI [Type of Narrator in Novel Telegram By Putu Wijaya: Narratology Approach] - A. Yusdianti Tenriawali (TOTOBUANG, 2018)
This study discusses the type of narrator in novel Telegram by Putu Wijaya. This study aims to identify the types of narrators contained in the novel Telegram by Putu Wijaya based on Mieke Bal's narratology theory. This research is qualitative research using descriptive methods. The data in this study are texts that are considered to represent the narrator in the novel Telegram. The source of the data in this study was the novel Telegram by Putu Wijaya, which was published in 1977. The data collection techniques in this study were the reading and note-taking techniques. The data analysis techniques in this study consist of four stages; narrator identification, narrator text classification, analysis, and description of the types of narrators in each chapter. The results showed that the type of narrator in the novel Telegram by Putu Wijaya consisted of an internal narrator (CN), a figure of Aku and Rosa, and an external narrator (EN), something that was unknown. The use of an internal narrator (CN) aims to give the impression that what is told in a story is real. The use of an external narrator (EN) aims to inform the reader that the story contained in the text that is being read is a fantasy, imagination, or imaginary story contained in the story or story that is being read.Penelitian ini membahas tipe narator dalam novel Telegram karya Putu Wijaya. Penelitian ini bertujuan mengidentifikasi jenis-jenis narator yang terdapat dalam novel Telegram karya Putu Wijaya berdasarkan teori naratologi Mieke Bal. Penelitian ini merupakan penelitian kualitatif dengan menggunakan metode deskriptif. Data berupa teks yang dianggap merepresentasikan narator dalam novel Telegram. Sumber data yakni novel Telegram karya Putu Wijaya yang terbit tahun 1977. Teknik pengumpulan data yakni teknik baca dan teknik catat. Adapun teknik analisis data terdiri atas empat tahap yaitu identifikasi narator, klasifikasi teks narator, analisis, dan deskripsi jenis-jenis narator tiap bab. Hasil penelitian menunjukkan bahwa tipe narator dalam novel Telegram karya Putu Wijaya terdiri atas narator internal (CN) yaitu tokoh Aku dan Rosa, serta narator eksternal (EN) yaitu sesuatu yang tidak diketahui identitasnya. Penggunaan narator internal (CN) bertujuan untuk memberi kesan bahwa yang diceritakan dalam suatu cerita adalah nyata. Adapun penggunaan narator eksternal (EN) bertujuan menyatakan kepada pembaca bahwa cerita yang terdapat dalam teks yang sedang dibacanya adalah suatu khayalan, imajinasi, atau cerita rekaan yang terdapat dalam kisah atau cerita yang sedang dibacanya.